THE ROLE OF THE CONCEPT OF "I" IN THE FORMATION OF PERSONALITY QUALITIES IN A CHILD (Scientific journal of the Fergana State University, 2024)
This article describes the role of the concept of "I" and its specific features in the formation of personal qualities in a child of preschool age. Approaches to this issue from the point of view of various theories and views of psychological scientists on this issue are analyzed. Foreign scientists R. Burns, W. James, I.S Kohn, Ch.H. Cooley, J.G Meade, K. Rogers, W.W. Stolin, K. Horney, T. Shibutani, E. Erikson, Russian scientists, L.N. Bojovich and N.I. Nepomnyashaya, V.S. Information on the theoretical and practical work of Mukhi on the formation of the personality and its characteristics and the role of the concept of "I" in it is presented. The process of the formation of the child's personality is related to the formation of the concept of "I" in the child and the spheres of its occurrence, that is, self-awareness, activity and its motivation, the process of interpersonal relations are considered as the main sources of the formation of the child's personality, and the formation of the phases of the child's personality in these areas The research conducted on its characteristics is analyzed. Empirical data on this problem has been analyzed.